RESITA NETWORK - Academic Entrepreneurship and Innovation Network of South Eastern European Universities: an Example of Successful Networking in Entrepreneurship and Innovation at Academic Level - Schulte, Peter; Živković, Dragana; Graef, Michael; Vadnjal, Jaka; Trisca, Gelu; Mihajlovic, Ivan; Pavlov, Daniel; Kume, Vasilika; Živković, Živan; Dimitrova, Makedonka; Zečić, Dževad; Halebić, Jasmin; et al. (Serbian Journal of Management, 2013)
The foundation, development, activities, and wider social impact of the Academic Entrepreneurship and Innovation Network of South Eastern European Universities, or shortly RESITA Network, is presented in this paper as a positive example of successful networking in entrepreneurship and innovation at academic level.